THE INFLUENCE OF LADY MACBETH TO MACBETH DOWNFALL IN SHAKESPEARE'S MACBETH - Meidy Maekel Moonik; Tini Mogea; Delli Sabudu (English Education Department, 2020)
This research intends to depict the influences of Lady Macbeth to Macbeth downfall, and the effect of Lady Macbeth influences to Macbeth. In doing this research, the writer uses objective approach. Objective approach is used because primary source of this research is literary work, the drama Macbeth. However, the analysis of drama Macbeth is based on the writer analysis and interpretation in accordance with the fact and evidences found in drama. By the analysing the topic, it is found out that, the downfall of Macbeth not only caused by his own weakness but also bad influences of Lady Macbeth as a wife. The analysis shows that Lady Macbeth not only supports her husband to make the prophecy became true, but Lady Macbeth has controlled the mind set of Macbeth. Lady Macbeth influences her husband to did the crime in order the prophecy about Macbeth will be a king of Scotland became true. Finally, Lady Macbeth influences her husband to murder King Duncan. In the end, Macbeth cannot happy to all that He got, He fell guilt, unhappy and uncomfortable.